The Parental Authority of the Minor and the Influence of Constitutional Guarantees in Ecuador: A Legal and Sociocultural Approach - Dc pc, Ab. María José Alcívar Quijano, Mg.; Tufiño, Karina Alejandra Haro; Urdanigo, Hector Eduardo Rangel (Journal of Posthumanism, 2025)
In Ecuador, parental authority has evolved to align with international standards on children's rights, emphasizing the shift from a parental right to a responsibility focused on the child's best interest, as established by the Convention on the Rights of the Child. The primary objective of this study was to analyze the legal framework of parental authority in Ecuador and its influence on constitutional guarantees related to children's rights, using a qualitative methodology centered on document analysis. The research aimed to explore the dynamics between parental authority and constitutional guarantees, integrating legal and sociocultural perspectives through the review of relevant legislation, jurisprudence, and academic literature. The findings highlight a complex interaction between parental authority and constitutional guarantees in Ecuador, revealing a progressive orientation of parental authority towards the welfare and best interest of the child. This aligns with constitutional principles and international commitments undertaken by Ecuador. However, significant challenges were identified in implementing these principles within the Ecuadorian sociocultural context, underscoring the need for legislative and practical adjustments to effectively protect children's rights. The study concludes that the continuous adaptation of the legal framework and public policies, along with proper training for legal operators, is crucial to ensure the effective protection of children's rights and a proper balance between parental authority and constitutional guarantees in Ecuador.